Character Education in the Zapin Anvaya Dance Learning Process at the Mataya Literary Studio in Sungai Pinang, Banyuasin - Melioktavia2 Rasnawati2 (Journal of Education and Teaching Learning, 2026)
Character education in the Zapin Anvaya dance learning process at the Mataya Literature Studio in Sungai Pinang Village, Banyuasin Regency, South Sumatra. This study used a qualitative descriptive approach. Data collection techniques included observation, interviews, and documentation. Data analysis referred to the Miles and Huberman model, which includes data reduction, data presentation, and conclusion drawing. The results showed that character education in Zapin Anvaya dance learning was integrated into every stage of the activity, from prayer and warm-up to movement practice, through evaluation. The character values ​​formed included honesty, religiousness, tolerance, cooperation, discipline, creativity, independence, and responsibility. These values ​​were instilled through habituation and direct experience during the learning process, rather than through theoretical presentation. Thus, Zapin Anvaya dance learning at the Mataya Literature Studio not only developed artistic skills but also contributed to the holistic character formation of students. This research is expected to serve as a reference in the development of character-based arts education models in both non-formal and formal environments